Sosialisasi Praktikum Fisika Materi Suhu dan Kalor di MAS Hajijah Amalia Sari Padangsidimpuan - Evitamala Siregar; Rizki Fadilah; Kasmawati (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
Physics is a learning that cannot be separated from practicum, physics if explained in theory alone will make students bored in learning physics. So that the purpose of doing this service is to motivate and provide new knowledge to students at the MAS Hajijah Amalia Sari Padangsidimpuan school regarding physics practicum on temperature and heat material and its application in everyday life. This activity was attended by 25 students. The method of implementing this activity is direct practice in providing learning material using Student Worksheets (LKS) as a guide in doing practicum in each material. Based on the results of the activities carried out, it can be concluded that using practicum makes students more enthusiastic and active in learning physics and changes the mindset of students that learning physics is not just memorizing formulas but can be fun learning if done with practicum to prove existing theory. And there was an increase in student scores in answering the questions in the first to fourth Student Worksheets (LKS1-4) so that students became more adept at carrying out practicum on temperature and heat material according to the steps in the student worksheets.